The Effects of Wearable Resistance on Shoulder Strength and Throwing Velocity in Baseball Pitchers - Job, Trey (Auckland University of Technology, 2025)
Throwing velocity is a key attribute for baseball pitchers. Accordingly, substantial effort has been dedicated to enhancing throwing velocity and its underlying characteristics. Wearable resistance (WR) for throwing athletes is a relatively new training method where micro-loads are attached to the throwing arm, allowing for load placement variation and deceleration phase overload, with the primary aim of sport specific strengthening of the throwing arm musculature. However, currently there is no research investigating WR utilisation to improve pitching performance. The overarching question of this thesis was what are the effects of throwing arm WR loading and training on shoulder strength and throwing velocity in pitchers? This thesis encompassed a series of acute studies and a training study to address the research question. Two studies quantified peak force (Fmax) and rate of force development (RFD) reliability during shoulder internal (IR) and external rotation (ER) with strain gauge technology. First, swimmers (n = 18) were evaluated in three testing positions, with acceptable Fmax reliability observed in all positions (coefficient of variation, CV = 5.2-8.8%, intraclass correlation coefficient 95% confidence intervals, ICC 95% CI = .69-.98), however, RFD reliability was questionable (CV = 11.5-18.1%, ICC 95% CI = .34-.96). Subsequently, college and high school (HS) pitchers (n=15) were assessed in the supine 90o position, which provided the least variability. IR Fmax reliability was found acceptable (CV = 5.8%, ICC 95% CI = .56-.95), ER Fmax reliability was mixed (CV = 4.3%, ICC 95% CI = .39-.93) and RFD reliability unacceptable (CV = 16-29%, ICC 95% CI = .41-.97). Relationships between shoulder rotator strength (Fmax and RFD during shoulder IR and ER) and throwing velocity was then explored. College and HS pitchers (n = 26) were assessed, the highest shared variance (adjusted R2 = .12-.13, p < .05) was between Fmax and throwing velocity. An acute WR throwing analysis with college and HS pitchers (n = 10) was used to quantify the effects of above and below elbow placement of WR (100-g, 150-g and 200-g) on throwing velocity, arm speed and temporal phase mechanics compared to unloaded trials. The effect of load on throwing velocity differed by placement with small to moderate reductions in throwing velocity (-1.8 to -2.7%, p < .01) detected with below elbow loads. Large decreases in arm speed (-5.1 to -6.5%, p < .05) with 150-g and 200-g below elbow were observed and the effects on temporal phase timing not clearly affected. College pitchers (n = 17) were randomly assigned to a control or upper-arm WR group using a matched-volume design, implemented two times per week over six weeks of training. Pre- and post-test training of shoulder rotator strength, range of motion (ROM) and throwing performance unveiled no clear changes (p > .05) in throwing performance or shoulder rotator strength in either group. ER ROM increased over time (p < .05), predominantly attributed to changes in the control group (+15.8%). There is not sufficient evidence to support the use of WR for improving shoulder strength or throwing velocity in pitchers, within the protocols employed in this research. Despite unclear results, practical findings regarding shoulder strength assessment and suggestions for training pitchers were included in an opinion piece, which provides direction for practitioners and future researchers.